EXPRESSION OF CERTAIN ACTIVATION MARKERS, CD45RA, CD45RO AND CD11B ON THE SURFACE OF PERIPHERAL BLOOD LYMPHOCYTES ISOLATED FROM PATIENT WITH IDIOPATHIC PRETERM LABOUR. (Iraqi Journal of Medical Sciences, 2016)
Background: preterm labor (PL) is remaining the leading cause of non-anomalous prei natal mortalities.Objective: is to determine the association of PL on the expression of certain activation markers on the surface of peripheral blood lymphocytes (PBLs).Patients and methods: Thirty patients with idiopathic pre term labour (IPL) (group A) in addition to 30 healthy pregnant women of comparable gestational age groups (group B) were enrolled in this study. Blood samples were taken from both groups and lymphocytes were separated and stained with fluorescent labeled monoclonal antibodies against CD45RA, CD45RO and CD11b.Results: results indicated that there were a significant increase in the percentage of CD45RA in group A and reduction in the percentage of both CD45RO and CD11b in the same group.Conclusions: patients with IPL have a less tendency of the activity of lymphocytes.Key words: Idiopathic premature labour, activation markers, CD45RA, CD45RO, CD11b.
Keywords: Idiopathic premature labour; activation markers; CD45RA; CD45RO; CD11b